THE IMPORTANCE OF IMAM TIRMIDHI’S ‘SUNAN’ IN ISLAMIC HISTORY - Jurayeva Ulmas Choriyevna (American Journals Publishing, 2024)
This article presents reflections on the life and hadith activities of Imam Termizi. It also makes scientific conclusions about the significance of Imam Termizi’s work ‘Sunan Termizi’ in the history of Islam and its role today.
Keywords: Imam Tirmidhi, hadith, Sunan, ‘Sunan Tirmidhi’, Termiz, history, Tirmidhis, Islam.